Climate change, resource degradation, and economic sustainability: A study of key commodity sectors in Southern Sumatra - Nopiah, Ririn; Azansyah, Azansyah; Ekaputri, Retno Agustina; Kumara, Bima Prasetya; Prasetya, Bayu Andy; Sunaryo, Sunaryo (Privietlab, 2025)
Climate change is one of the biggest challenges facing the world today. This phenomenon has significantly impacted the degradation of natural resources, posing a serious threat to the agricultural and fisheries sectors, especially in developing countries. Climate change affects the structure of land and water and directly impacts the potential sectors in a region. The primary objective of this study is to quantitatively analyze the impact of climate change on resource degradation across the leading commodity sectors, namely agriculture, plantations, and fisheries in the Southern Sumatra region. This research adopts a mixed-methods approach, integrating multiple regression analysis using regional data from 2015 to 2022 with a Sharing Group Discussion (SGD) component to ensure contextual validation and deeper insights. The findings indicate that six meteorological factors (wind speed, rainfall, solar radiation, air temperature, air pressure, and humidity) significantly influenced degradation within these three crucial sectors. Ultimately, this study offers a forecasting overview of the climate impacts on specific commodity sectors, providing a crucial basis for stakeholders to formulate anticipatory policies, plan appropriate technological adaptation, and implement more effective resource management strategies to address the challenges of climate change.